Broken Windows Policing and Constructions of Public Order and Safety: Based on the New York Miracle - Wang, Jingjing (International Journal of Social Sciences and Public Administration, 2024)
Broken windows theory, as one of the most famous and influential theories, was developed by JQ Wilson and George Kelling in 1982. Their thesis was that, if human ’broken windows’ are not fixed, disorder will turn into serious crime because ’serious street crime flourishes in areas in which disorderly behavior goes unchecked’ (Wilson and Kelling 1982:34). It was soon applied in many aspects of the society and most of them achieved good results.Among these applications of broken window theory, it has to mentioned the ‘New York Miracle’, which greatly dropped down the crime rate in New York in 1990s. But,broken windows theory is not simply applied in the case of New York. Instead, a variant of broken windows theory called theory ‘zero tolerance’ played a major role in controlling crime rate. Although ‘zero tolerance’ is similar with broken window theory, the prior focus on more on the law enforcement. The wide application of zero tolerance also triggers many researchers’ negative responses, who doubt the success of the realness of ‘New York Miracle’ and the validity of zero tolerance policing. Therefore, in this paper, we are going to analyze both the advantage and disadvantage of the zero-tolerance policing, and further discuss the effectiveness of the cooperation between the police and community and the situational crime prevention.